ANALISIS PEMIKIRAN EKONOMI ISLAM DI INDONESIA - Daulay, Diah Hanifah; Salwa, Andin Charisa (Journal of Management, Economic and Accounting (JMEA), 2025)
This research is the result of a literature review on Islamic economic thought in Indonesia. This research is explained by the main figures namely H.O.S. Tjokroaminoto who represents the pre independence era, Sjafruddin Prawiranegara for the Old Order period, and A.M Saefuddin for the New Order period. Islamic economics is an economic system that runs based on the provisions of sharia and makes the Qur'an and As-Sunnah as the main legal reference source, this system develops from era to era, as well as from the time of the Prophet Muhammad Saw until the time of Islamic economic thought of Muslim scholars.